A DC-DC circuit using boost converter for low voltage energy harvesting application - Arfah, Nurul; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (Science Publications, 2015)
A DC-DC step-up voltage converter is designed to convert a very lowvoltage supply, 35 mV such as fromthe thermal energy source from body heat. The converter can generate an outputvoltage up to 210 mV, approximately six imes its initial input voltage over afrequency of 36 GHz. The effect of switching transistors, inductor current,rise and fall time is also highlighted. The circuit operates using 2 µH inductor and 0.01 fF load capacitor, is simulated usingPSpice Simulation tool. This voltage converter is suitable for energyharvesting application in implanted electronic devices.